Brain structural changes in subjective cognitive decline: A whole brain surface‐based analysis in the FACEHBI cohort. (1st February 2022) - Alonso‐Lana, Silvia; Sotolongo‐Grau, Oscar; Tartari, Juan Pablo; Sanabria, Angela; Alarcón‐Martín, Emilio; Valero, Sergi; Montrreal, Laura; Orellana, Adelina; de Rojas, Itziar; Vivas, Assumpta; Tejero, Miguel Angel; Gómez‐Chiari, M.; et al.
Abstract: Background: Subjective cognitive decline (SCD) has been associated with increased risk of subsequent mild cognitive impairment (MCI) and dementia. Evidence from magnetic resonance imaging studies shows that neurodegenerative changes are already present years before dementia and thus, examining brain changes in SCD may contribute to identify potential biomarkers at an early stage of Alzheimer's disease. Method: 198 individuals with SCD from the FACEHBI cohort were included (124 females; mean age 65.76 years). All subjects underwent magnetic resonance imaging and 18F‐Florbetaben positron emission tomography scan at baseline and were clinically follow‐up. Whole‐brain cortical surface‐based morphometry analysis were conducted using Freesurfer. Changes in cortical morphology (cortical thickness and surface area) were examined in relation to age, gender, brain amyloid beta deposition, ApoE‐e4 status (52 carrier/ 146 non carrier) and progression to MCI or dementia at the 4‐year follow‐up. Age, sex and years of education were included as covariates in all analyses. Result: At p=0.05 corrected, higher age was associated with widespread cortical thickness reduction and reduced surface area in bilateral parahippocampal, left cuneus and middle frontal and in the right superior frontal cortex. Males had reduced cortical thickness in the right lingual and reduced surface area in the right superior temporal cortex. Higher amyloid beta deposition was related to higher surface area in the left inferior parietal cortex and no significant results were found in relation to ApoE‐e4 status. At the 4‐year follow‐up, 33 subjects had progressed to MCI and 118 remained cognitively unimpaired, but there were no significant differences in baseline cortical thickness or surface area between them. With a liberal threshold of p<0.0001 uncorrected, we found a cluster of reduced cortical thickness in the right isthmus cingulate in those who converted to MCI four years later. Conclusion: Brain morphological changes in SCD are mainly characterized by cortical thickness reduction in relation to age and increased left inferior parietal surface area in relation to higher brain amyloid burden. Baseline reduced cortical thickness in the right isthmus cingulate is the only region associated with subsequent clinical progression to MCI and thus, it might be a useful predictive biomarker of cognitive decline in SCD individuals.